Wykorzystanie LCA (Life Cycle Assessment) do oceny środowiskowej budynku - Adamczyk, Janusz
The necessity to pursue the dynamic development of the construction industry for social reasons, as well as the fact that building new objects, using them and liquidating play a crucial part in increasing the ecological hazards, became a stimulus for searching new assessment instruments measuring the influence of this activity area on the environment in a complex way.
Keywords: ocena cyklu życia (istnienia); rozrachunek ekonomiczno-środowiskowy; oddziaływanie budynku na środowisko; budownictwo; budownictwo zrównoważone